Answer:
The equation in the slope-intercept form is y =
+ -6 ⇒ C
Explanation:
The slope-intercept form of the linear equation is
y = m x + b, where
- m is the slope of the line
∵ The equation is 13x - 3y = 18
→ At first move x from the left side to the right side by subtracting 13x
from both sides
∴ 13x - 13x - 3y = 18 - 13x
∴ - 3y = 18 - 13x
→ Make the coefficient of y equal 1 by dividing both sides by -3
∵
![(-3y)/(-3)=(18)/(-3)-(13x)/(-3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/deqz7ymgz907d0036hg3cnauickikakwvo.png)
∴ y = -6 - (
)
→ Remember (-)(-) = (+)
∴ y = -6 +
![(13)/(3)x](https://img.qammunity.org/2021/formulas/mathematics/high-school/18pvtg59x3vis8a6kbeoxbw5yrp68655mc.png)
→ Switch the two terms of the right side
∴ y =
+ - 6
∴ The equation in the slope-intercept form is y =
+ -6